Using 3D Bioprinted Autologous Minimally Manipulated Homologous Adipose Tissue for Limb Salvage in Treating Diabetic Foot Ulcer - Yoon, Hyeon Min; Song, Woo Jin (Archives of Plastic Surgery, 2024)
Reconstructive surgeons face challenges when considering limb salvage methods for the treatment of diabetic foot ulcers (DFUs). In this article, we present our experience with autologous fat grafting as a viable alternative in cases where flap reconstruction is difficult. We encountered a 78-year-old female patient with a nonhealing DFU who had multiple comorbidities, including renal failure and severe peripheral arterial disease. During the initial multidisciplinary meeting, due to extensive necrosis and osteomyelitis, amputation was recommended. However, the patient expressed a strong preference for a salvage procedure and refused amputation. After careful consideration, we opted to reconstruct the patient's foot using three-dimensional bioprinted autologous minimally manipulated homologous adipose tissue. The AMHAT was engrafted well without complications such as autolysis, graft failure, or infection. After the operation, the large defect with partial bone exposure was covered with healthy granulation tissue. The size of the wound decreased to less than half its original size after 6 weeks of surgery, and it decreased to less than 25% after 12 weeks of surgery. The AMHAT may be an appealing treatment option for diabetic foot patients who are unsuitable for flap reconstruction due to comorbidities.
Keywords: adipose tissue; bioprinting; diabetic foot; limb salvage